The Application of Wearable Glucose Sensors in Point-of-Care Testing - Zhang, Sheng; Zeng, Junyan; Wang, Chunge; Feng, Luying; Song, Zening; Zhao, Wenjie; Wang, Qianqian; Liu, Chen (Frontiers in Bioengineering and Biotechnology, 2021)
Diabetes and its complications have become worldwide diseases which influence the human health negatively and even lead to death. The real-time and convenient glucose detection in biofluid is badly needed. The traditional glucose testing is detecting in the blood and invasive, which can not be constinuous and result in discomfort for the users. Consequently, wearable glucose sensors towards point-of-care glucose testing in biofluid have atractted great attention and trend of the glucose testing is from invasive to noninvasive. In this review, the wearable point-of-care glucose sensors for the detection of different biofluids inluding blood, sweat, saliva, tears, and interstitial fuild are discussed and the future trend of development is prospected.